2021
DOI: 10.1002/alr.22791
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of silastic sheet nasal splints in endoscopic nasal septal repair surgery: a prospective, randomized, single‐blinded controlled trial

Abstract: Javer AR. The efficacy of silastic sheet nasal splints in endoscopic nasal septal repair surgery: a prospective, randomized, single-blinded controlled trial. Int

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…They proceed to conclude that splints do not significantly change surgical outcome and can be avoided if need-be. 14 However, contrary to the studies previously mentioned and to our results, von Schoenberg et al found an increased incidence of intranasal adhesions in patients without splints. They used Exmoorsilastic plastic standard-size splints in their study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…They proceed to conclude that splints do not significantly change surgical outcome and can be avoided if need-be. 14 However, contrary to the studies previously mentioned and to our results, von Schoenberg et al found an increased incidence of intranasal adhesions in patients without splints. They used Exmoorsilastic plastic standard-size splints in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…These exceptional scenarios when splints can/should be considered include compromise to the septal flap, large bleeding tear in the septum, injury to the turbinates and patients at increased risk of adhesions. 14 Limitation of this study includes a relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study's relevance and significance in current medical literature rely on acknowledging the widespread use of ISS in septoplasty surgeries, which has generated interest and debate among professionals due to its impact on postoperative outcomes. 3,33 Deciding whether to adopt ISS routinely or selectively has led to varying practices across medical centres. Comparing recent techniques involving transseptal sutures to nasal packing, including ISS, studies have demonstrated the superiority of transseptal sutures in reducing postoperative pain and complications like epiphora, sleep disturbance, and dyspnea.…”
Section: Final Considerationsmentioning
confidence: 99%